Biochemical Characterization of Putative Adenylate Dimethylallyltransferase and Cytokinin Dehydrogenase from Nostoc sp. PCC 7120 - Frébortová, Jitka; Greplová, Marta; Seidl, Michael F; Heyl, Alexander; Frébort, Ivo (PloS one, 2015)
Cytokinins, a class of phytohormones, are adenine derivatives common to many different organisms. In plants, these play a crucial role as regulators of plant development and the reaction to abiotic and biotic stress. Key enzymes in the cytokinin synthesis and degradation in modern land plants are the isopentyl transferases and the cytokinin dehydrogenases, respectively. Their encoding genes have been probably introduced into the plant lineage during the primary endosymbiosis. To shed light on the evolution of these proteins, the genes homologous to plant adenylate isopentenyl transferase and cytokinin dehydrogenase were amplified from the genomic DNA of cyanobacterium Nostoc sp. PCC 7120 and expressed in Escherichia coli. The putative isopentenyl transferase was shown to be functional in a biochemical assay. In contrast, no enzymatic activity was detected for the putative cytokinin dehydrogenase, even though the principal domains necessary for its function are present. Several mutant variants, in which conserved amino acids in land plant cytokinin dehydrogenases had been restored, were inactive. A combination of experimental data with phylogenetic analysis indicates that adenylate-type isopentenyl transferases might have evolved several times independently. While the Nostoc genome contains a gene coding for protein with characteristics of cytokinin dehydrogenase, the organism is not able to break down cytokinins in the way shown for land plants.
Keywords: prenyltransferáza; cytokininy; Dimethylallyltranstransferase; biologická evoluce; Sequence Homology, Amino Acid; Nostoc; fylogeneze; Gene Expression Regulation, Enzymologic; Recombinant Proteins; Mutagenesis, Site-Directed; Molecular Sequence Data; geneticky modifikované rostliny; sekvence aminokyselin; Mutation; tabák; mutageneze cílená; Cytokinins; regulace genové exprese enzymů; sekvenční homologie aminokyselin; Oxidoreductases; Plants, Genetically Modified; rekombinantní proteiny; Phylogeny; Nicotiana; oxidoreduktasy; mutace; Biological Evolution; Amino Acid Sequence; Escherichia coli; molekulární sekvence - údaje